Preparation method of a type of naphthyl polycarboxylate organic material and its application in metal ion batteries

By crosslinking the naphthyl compound of naphthyl polycarboxylate organic material with carbon-based material, a negative electrode material with rich carboxylate active sites and high conductivity is formed, which solves the problem of insufficient performance of the negative electrode material in the prior art. It achieves efficient metal ion storage and battery stability improvement.

CN115954444BActive Publication Date: 2025-01-14SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211326576.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-01-14
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The negative electrode material performance of existing metal ion batteries is insufficient, resulting in limited storage capacity and poor cycle stability, which cannot meet actual needs.

Method used

Naphthyl polycarboxylate organic material is used as the negative electrode active material, and the crosslinking of naphthyl compounds and carbon-based materials form rich carboxylate active sites and electron conductivity, improving the capacity of storing metal ions and the long cycle performance of the battery and stability.

Benefits of technology

It achieves a high specific capacity and long cycle performance, reduces the volume expansion problem during battery cycle, improves the chemical stability and conductivity of the material, and meets the actual demand of metal ion storage capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115954444B_ABST
    Figure CN115954444B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a type of naphthyl polycarboxylate organic material and its application in metal ion batteries. In the first aspect of the present application, a naphthyl polycarboxylate organic material is provided, comprising a naphthyl compound and a carbon-based material cross-linked with the naphthyl compound. The naphthyl compound has abundant carboxylate active sites, which can effectively store metal ions and improve the capacity of storing metal ions; at the same time, the carbon-based material cross-linked with the naphthyl compound through aromatic stacking as a support for the naphthyl polycarboxylate organic material is not only conducive to enhancing electronic conductivity, but also improves the chemical stability of the material. When it is used as a negative electrode active material of a metal ion battery, it can obtain good specific capacity, long cycle performance and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic materials, and in particular to a method for preparing a type of naphthyl polycarboxylate organic material and its application in metal ion batteries. Background Art

[0002] Due to the limited total amount of fossil energy, clean energy such as solar energy, wind energy, and tidal energy are gradually being developed and utilized by people. However, these clean energy sources are intermittent and regional, and need to be combined with corresponding energy storage technologies to complete energy storage. Among various energy storage technologies, electrochemical energy storage has a high conversion rate and is flexible to use, and has become the current mainstream technology. Among them, metal ion batteries represented by lithium-ion batteries are the current research hotspot. However, the current problem is that the storage capacity of these metal ion batteries still cannot meet the needs of actual production and life, and the negative electrode, as an important component of metal ion batteries, has an important influence on the various indicators of the battery. Therefore, finding suitable negative electrode materials to store metal ions is of great significance to promoting the development of new metal ion batteries.

[0003] At present, inorganic negative electrode materials represented by intercalation carbon-based materials, alloy metal materials (aluminum, tin and germanium, etc.), and intercalation conversion transition metal oxide materials have been widely used in metal ion storage research. However, the metal ion storage capacity of carbon materials is limited, and the cycle process is prone to cause intercalation expansion, which reduces the battery cycle stability; metal materials cause serious volume expansion during the alloying process, and even cause electrode pulverization, resulting in insufficient battery cycle performance; transition metal oxides / sulfides have poor conductivity and reversibility, which leads to serious attenuation of battery cycle performance. Compared with the above-mentioned inorganic materials, organic materials have the advantages of flexible design and a wide variety, and are considered to be negative electrode materials with great application potential. For example, it has been reported that 4,4',4"-triaminotriphenylmethane and 1,4,5,8-naphthalenetetracarboxylic anhydride are used as raw materials to react to obtain pure organic polymers for lithium storage. However, although the negative electrode material has a novel structure and is used in battery positive electrode materials for the first time, it exhibits poor lithium storage performance and insufficient cycle stability. Therefore, it is necessary to provide a material that has good specific capacity when used as a negative electrode material and can improve the long cycle performance and stability of the battery. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a method for preparing a naphthyl polycarboxylate organic material and its application in a metal ion battery. The naphthyl polycarboxylate organic material has good specific capacity when used as a negative electrode active material of a metal ion battery, and can improve the long cycle performance and stability of the battery.

[0005] In a first aspect of the present application, a naphthyl polycarboxylate organic material is provided, comprising a naphthyl compound and a carbon-based material cross-linked with the naphthyl compound, wherein the structural formula of the naphthyl compound is as follows:

[0006]

[0007] Wherein, R and R′ are independently selected from at least one of hydrogen, halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl, sulfonic acid, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C3 alkoxy, and the substituent of C1-C3 alkyl and C1-C3 alkoxy is selected from at least one of halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl, and sulfonic acid;

[0008] x and y are independently selected from integers of 0 to 4, and x and y are not 0 at the same time;

[0009] M 1 and M 2 are independently selected from hydrogen and alkali metals, and x M 1 and y M 2 Not hydrogen at the same time.

[0010] The naphthyl polycarboxylate organic material according to the embodiment of the present application has at least the following beneficial effects:

[0011] For the naphthyl polycarboxylate organic material, the naphthyl compound therein has abundant carboxylate active sites, which can effectively store metal ions and improve the capacity of storing metal ions; at the same time, the carbon-based material cross-linked with the naphthyl compound through aromatic stacking as the support of the naphthyl polycarboxylate organic material is not only conducive to enhancing the electronic conductivity, but also improves the chemical stability of the material. When it is used as the negative electrode active material of the metal ion battery, it can obtain good specific capacity, long cycle performance and stability.

[0012] In some embodiments of the present application, R and R' are each hydrogen.

[0013] In some embodiments of the present application, x and y are independently selected from integers of 1 to 3. For example, x=1, y=1; x=1, y=2; x=1, y=3; x=2, y=1; x=2, y=2; x=2, y=3; x=3, y=1; x=3, y=2; x=3, y=3.

[0014] In some embodiments of the present application, the naphthyl compound is selected from 1-naphthoic acid, 2-naphthoic acid, 3-naphthoic acid, 4-naphthoic acid, 5-naphthoic acid, 6-naphthoic acid, 7-naphthoic acid, 8-naphthoic acid, 1,2-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 1,7-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,4-naphthalene dicarboxylic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 2,8-naphthalene dicarboxylic acid, 3,4-naphthalene dicarboxylic acid, 3,5-naphthalene dicarboxylic acid, 3,6-naphthalene dicarboxylic acid, 3,7-naphthalene dicarboxylic acid, 3,8-naphthalene dicarboxylic acid, 4,5-naphthalene dicarboxylic acid, 4,6-naphthalene dicarboxylic acid, 4,7-naphthalene dicarboxylic acid, 4,8-naphthalene dicarboxylic acid, 5,6-naphthalene dicarboxylic acid, 5,7-naphthalene dicarboxylic acid, 5,8-naphthalene dicarboxylic acid, 6,7-naphthalene dicarboxylic acid, 6,8-naphthalene dicarboxylic acid, 7,8-naphthalene dicarboxylic acid, 1,2,3-naphthalene tricarboxylic acid, 1,2,4-naphthalene tricarboxylic acid, 1,2,5-naphthalene tricarboxylic acid, 1,2,6-naphthalene tricarboxylic acid, 1,2,7-naphthalene tricarboxylic acid, 1,2,8-naphthalene tricarboxylic acid, 1,3,4-naphthalene tricarboxylic acid, 1,3,5-naphthalene tricarboxylic acid, 1,3,6-naphthalene tricarboxylic acid, 1,3,7-naphthalene tricarboxylic acid, 1,3,8-naphthalene tricarboxylic acid, 1,4,5-naphthalene tricarboxylic acid, 1,4,6-naphthalene tricarboxylic acid, 1,4,7-naphthalene tricarboxylic acid, 1,4,8-naphthalene tricarboxylic acid, 1,5,6-naphthalene tricarboxylic acid, 1 ,5,7-naphthalenetricarboxylic acid, 1,5,8-naphthalenetricarboxylic acid, 1,6,7-naphthalenetricarboxylic acid, 1,6,8-naphthalenetricarboxylic acid, 1,7,8-naphthalenetricarboxylic acid, 2,3,4-naphthalenetricarboxylic acid, 2,3,5-naphthalenetricarboxylic acid, 2,3,6-naphthalenetricarboxylic acid, 2,3,7-naphthalenetricarboxylic acid, 2,3,8-naphthalenetricarboxylic acid, 2,4,5-naphthalenetricarboxylic acid, 2,4, 6-naphthalenetricarboxylic acid, 2,4,7-naphthalenetricarboxylic acid, 2,4,8-naphthalenetricarboxylic acid, 2,5,6-naphthalenetricarboxylic acid, 2,5,7-naphthalenetricarboxylic acid, 2,5,8-naphthalenetricarboxylic acid, 2,6,7-naphthalenetricarboxylic acid, 2,6,8-naphthalenetricarboxylic acid, 2,7,8-naphthalenetricarboxylic acid, 3,4,5-naphthalenetricarboxylic acid, 3,4,6-naphthalenetricarboxylic acid, 3,4,7-naphthalenetricarboxylic acid Tricarboxylic acid, 3,4,8-naphthalenetricarboxylic acid, 3,5,6-naphthalenetricarboxylic acid, 3,5,7-naphthalenetricarboxylic acid, 3,5,8-naphthalenetricarboxylic acid, 3,6,7-naphthalenetricarboxylic acid, 3,6,8-naphthalenetricarboxylic acid, 3,7,8-naphthalenetricarboxylic acid, 4,5,6-naphthalenetricarboxylic acid, 4,5,7-naphthalenetricarboxylic acid, 4,5,8-naphthalenetricarboxylic acid, 4,6,7-naphthalenetricarboxylic acid , 4,6,8-naphthalenetricarboxylic acid, 4,7,8-naphthalenetricarboxylic acid, 5,6,7-naphthalenetricarboxylic acid, 5,6,8-naphthalenetricarboxylic acid, 5,7,8-naphthalenetricarboxylic acid, 6,7,8-naphthalenetricarboxylic acid, 1,2,3,4-naphthalenetetracarboxylic acid, 1,2,3,5-naphthalenetetracarboxylic acid, 1,2,3,6-naphthalenetetracarboxylic acid, 1,2,3,7-naphthalenetetracarboxylic acid, 1,2,3,8-naphthalenetetracarboxylic acid, 1,2,4,5-naphthalenetetracarboxylic acid, 1,2,4,6-naphthalenetetracarboxylic acid, 1,2,4,7-naphthalenetetracarboxylic acid, 1,2,4,8-naphthalenetetracarboxylic acid, 1,2,5,6-naphthalenetetracarboxylic acid, 1,2,5,7-naphthalenetetracarboxylic acid, 1,2,5,8-naphthalenetetracarboxylic acid, 1,2,6,7-naphthalenetetracarboxylic acid, 1,2,6,8-naphthalenetetracarboxylic acid…at least one alkali metal salt thereof, or at least one R or R′ is halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl, sulfonic acid, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C3 alkoxy, and the substituent is selected from at least one of halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl and sulfonic acid. The alkali metal salt refers to at least one carboxylic acid group of the naphthyl carboxylic acid being neutralized with an alkali metal base or substituted with an alkali metal salt.

[0015] In some embodiments of the present application, the naphthyl compound is selected from 1,4,5,8-naphthalenetetracarboxylic acid, 1-naphthalenecarboxylic acid, 2-naphthalenecarboxylic acid, 1,4-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 1,8-naphthalene dicarboxylic acid, 1,3,5-naphthalene tricarboxylic acid, 1,4,5-naphthalene tricarboxylic acid, 2,4,5-naphthalene tricarboxylic acid, 1,4,7-naphthalene tricarboxylic acid, 1,2,8-naphthalene tricarboxylic acid, 1,3,5,7-naphthalene tetracarboxylic acid, 1,2,3,4-naphthalene tetracarboxylic acid. 、1,4,6,7-naphthalenetetracarboxylic acid、2,3,6,7-naphthalenetetracarboxylic acid、1,2,3,4,5-naphthalenepentacarboxylic acid、1,2,3,4,6-naphthalenepentacarboxylic acid、1,2,3,6,7-naphthalenepentacarboxylic acid、1,2,3,5,8-naphthalenepentacarboxylic acid、1,2,4,5,8-naphthalenepentacarboxylic acid、1,2,4,5,6,8-naphthalenehexacarboxylic acid、1,2,3,4,5,8-naphthalenehexacarboxylic acid、1,2,3,4,6,7-naphthalenehexacarboxylic acid、1,2,3,4, 5,6,7-naphthalene heptacarboxylic acid, 1,2,3,4,5,6,8-naphthalene heptacarboxylic acid, 1,2,3,4,5,6,7,8-naphthalene octacarboxylic acid, 5-chloro-1-naphthalenecarboxylic acid, 5-amino-1-naphthalenecarboxylic acid, 6-hydroxy-2-naphthalenecarboxylic acid, 5,8-dihydroxy-2-naphthalenecarboxylic acid, 6-sulfonyl-2-naphthalenecarboxylic acid, 4-nitro-1,8-naphthalene dicarboxylic acid, 6-bromo-1,4-naphthalene dicarboxylic acid, 3-formyl-1,5-naphthalene dicarboxylic acid, 2-iodo-1,4,5-naphthalene tricarboxylic acid An alkali metal salt of at least one of the following: acid, 3-carbonyl-1,5,8-naphthalenetricarboxylic acid, 2-mercapto-1,4,5-naphthalenetricarboxylic acid, 3-hydroxy-1,5,8-naphthalenetricarboxylic acid, 2-methyl-1,4,5,8-naphthalenetetracarboxylic acid, 6-cyano-1,2,3,4-naphthalenetetracarboxylic acid, 2-ethyl-1,4,5,6,8-naphthalenepentacarboxylic acid, 6-chloro-1,2,3,4,5,8-naphthalenehexacarboxylic acid, and 6-acetic-1,2,3,4,5,7,8-naphthaleneheptacarboxylic acid.

[0016] In some embodiments of the present application, the naphthyl compound is selected from at least one alkali metal salt of 1,3,5-naphthalenetricarboxylic acid, 1,4,5-naphthalenetricarboxylic acid, 1,5,8-naphthalenetricarboxylic acid, 1,3,5,7-naphthalenetetracarboxylic acid, 1,4,6,7-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 1,2,3,4,6-naphthalenepentacarboxylic acid, 1,2,3,5,8-naphthalenepentacarboxylic acid, 1,2,4,5,8-naphthalenepentacarboxylic acid, 1,2,4,5,6,8-naphthalenehexacarboxylic acid, 1,2,3,4,5,8-naphthalenehexacarboxylic acid, 1,2,3,4,6,7-naphthalenehexacarboxylic acid, and 1,2,3,4,5,6,7,8-naphthaleneoctacarboxylic acid.

[0017] In some embodiments of the present application, the carbon-based material is selected from at least one of carbon nanotubes, carbon nanofibers, soft carbon, hard carbon, graphite, and graphene.

[0018] Among them, carbon nanotubes (CNTs) refer to one-dimensional quantum materials in which graphene sheets with radial dimensions at the nanometer level and axial dimensions at the micrometer level form a cylinder. According to the number of graphene sheets, they can be divided into single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). Carbon nanofibers (CNF) are quasi-one-dimensional carbon materials between carbon nanotubes and carbon fibers. Soft carbon refers to carbon materials that will be fully graphitized after high-temperature treatment, including but not limited to coke, mesophase carbon microbeads, carbon fibers, etc.; while hard carbon refers to carbon materials that are difficult to graphitize under high-temperature treatment, which can at least be obtained by pyrolysis of resins (such as phenolic resins, epoxy resins, polysaccharide alcohols, etc.), polymers (such as PFA, PVC, PVDF, PAN, etc.), carbon black, and biomass. Graphite includes but is not limited to natural graphite and artificial graphite. Graphene includes but is not limited to single-layer graphene, double-layer graphene, few-layer graphene (3 to 10 layers), multi-layer graphene (more than 10 layers), and also includes graphene oxide, reduced graphene oxide, etc.

[0019] In some embodiments of the present application, the carbon-based material is a carbon nanotube.

[0020] In some embodiments of the present application, the carbon-based material is a single-walled carbon nanotube.

[0021] In some embodiments of the present application, based on the total weight of the naphthyl polycarboxylate organic material, the content of the carbon-based material is 1-10wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%. Further, the content of the carbon-based material is 2-9wt%, 3-8wt%, 4-7wt%.

[0022] In a second aspect of the present application, a method for preparing a naphthyl polycarboxylate organic material is also provided, the preparation method comprising the following steps:

[0023] The carbon-based material, naphthyl carboxylic acid and alkali metal source are mixed in a liquid phase, reacted at 80-180° C. for 12-72 hours, separated and dried to obtain the naphthyl polycarboxylate organic material.

[0024] In some embodiments of the present application, mixing the carbon-based material, naphthyl carboxylic acid and the metal source in a liquid phase comprises:

[0025] Adding the dispersion of the carbon-based material dropwise into the solution of naphthyl carboxylic acid and mixing well to obtain a first mixed solution;

[0026] The metal source solution is added dropwise into the first mixed solution and mixed evenly to obtain a second mixed solution.

[0027] In some embodiments of the present application, the alkali metal source is a base or a salt of an alkali metal.

[0028] In some embodiments of the present application, the alkali metal source is an alkali metal base.

[0029] In some embodiments of the present application, the alkali metal of the alkali metal source is any one of lithium, sodium, and potassium. Different alkali metals are selected for different metal ion batteries. For example, for lithium ion batteries, a lithium source is selected; for sodium ion batteries, a sodium source is selected; for potassium ion batteries, a potassium source is selected.

[0030] In some embodiments of the present application, the alkali metal source is selected from lithium nitrate, lithium chloride, lithium sulfate, lithium hydroxide, sodium nitrate, sodium chloride, sodium sulfate, sodium hydroxide, potassium nitrate, potassium chloride, potassium sulfate, potassium hydroxide, and the like.

[0031] In some embodiments of the present application, the lithium source is lithium hydroxide, the sodium source is sodium hydroxide, and the potassium source is potassium hydroxide.

[0032] In some embodiments of the present application, the liquid phase is selected from at least one of anhydrous ethanol, ethylene glycol, glycerol, NN dimethylformamide, dimethyl sulfoxide, acetone, and deionized water.

[0033] In some embodiments of the present application, the molar ratio of the alkali metal source to the carboxylic acid group in the naphthyl carboxylic acid is (0.5-12):1.

[0034] In some embodiments of the present application, the molar ratio of the alkali metal source to the carboxylic acid group in the naphthyl carboxylic acid is (2-12):1.

[0035] In some embodiments of the present application, the preparation method comprises the following steps:

[0036] Dissolving an alkali metal source in a first solvent and stirring the solution with a magnetic force for 0.5 to 2 hours to obtain an alkali metal source solution;

[0037] Dissolving naphthyl carboxylic acid in a second solvent, and stirring magnetically for 0.5 to 2 hours to obtain a naphthyl carboxylic acid solution;

[0038] Taking a carbon-based material, adding it to a third solvent, and ultrasonicating and / or stirring until dispersed to obtain a dispersion of the carbon-based material;

[0039] Slowly adding the dispersion of the carbon-based material to the solution of naphthyl carboxylic acid drop by drop using a dropper, stirring for 0.5 to 4 hours to obtain a first mixed solution;

[0040] Under stirring, slowly adding the solution of the alkali metal source dropwise into the first mixed solution, and continuing stirring for 1 to 6 hours to obtain a second mixed solution;

[0041] The second mixed solution is reacted in a reaction kettle at 80 to 180° C. for 12 to 72 hours to obtain a reaction solution in which the reaction is completed;

[0042] After the reaction solution is cooled to room temperature, centrifuge at 7000-11000 rpm for 6-12 minutes, wash with ethanol, and repeat centrifugation for 3-5 times, and dry at 60-90° C. for 12-72 hours to obtain a naphthyl polycarboxylate organic material.

[0043] In some embodiments of the present application, the first solvent is anhydrous ethanol.

[0044] In some embodiments of the present application, the second solvent is an acetone aqueous solution.

[0045] In some embodiments of the present application, the volume ratio of acetone to water in the second solvent is about 10:3.

[0046] In some embodiments of the present application, the third solvent is anhydrous ethanol.

[0047] In some embodiments of the present application, the ultrasonic power required to disperse the carbon-based material into the third solvent is 50-60 kW, further about 53 kW.

[0048] In some embodiments of the present application, after the dispersion of the carbon-based material is added dropwise to the solution of the naphthyl carboxylic acid, the stirring time is continued for 1 to 3 hours, and further for about 2 hours.

[0049] In some embodiments of the present application, after the solution of the alkali metal source is added dropwise into the first mixed solution, stirring is continued for 3 to 5 hours, and further for about 4 hours.

[0050] In some embodiments of the present application, the reaction temperature is 80-120° C., and the reaction time is 12-48 hours; further, the reaction temperature is about 100° C. for 24 hours.

[0051] In some embodiments of the present application, the centrifugal speed before ethanol washing is 8000-10000 rpm, and the centrifugation is performed for 8-12 minutes; further, the centrifugal speed is about 9000 rpm, and the centrifugation is performed for 10 minutes.

[0052] In some embodiments of the present application, the drying temperature is 60° C. and the drying time is 48 hours.

[0053] The third aspect of the present application provides a pole piece, which includes a current collector and an active layer located on the current collector, and the raw material of the active layer includes the aforementioned naphthyl polycarboxylate organic material or the naphthyl polycarboxylate organic material prepared according to the aforementioned preparation method.

[0054] In some embodiments of the present application, the current collector includes but is not limited to metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or at least one of the alloy foils of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or at least one of the alloy meshes of the above metals).

[0055] In some embodiments of the present application, the raw material of the active layer further includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to at least one of graphite, acetylene black, carbon black, carbon nanotubes, carbon fibers, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyurethane (PU), polyvinyl alcohol (PVA), polyvinyl butyral (PVB), etc.

[0056] In some embodiments of the present application, the raw material of the active layer includes 50 to 99 wt % of a positive electrode active material, 0.5 to 40 wt % of a conductive agent, and 0.5 to 20 wt % of a binder.

[0057] In some embodiments of the present application, the method for preparing the electrode sheet includes preparing raw materials including naphthyl polycarboxylate organic material into slurry, coating the slurry on a current collector, and drying the slurry to obtain a negative electrode sheet having an active layer.

[0058] In a fourth aspect of the present application, a metal ion battery is provided, wherein the metal ion battery comprises the aforementioned electrode sheet.

[0059] In some embodiments of the present application, the metal ion battery includes at least one of a lithium ion battery, a sodium ion battery, a potassium ion battery, and the like.

[0060] In some embodiments of the present application, the above-mentioned electrode sheet is used as a negative electrode sheet.

[0061] In some embodiments of the present application, the metal ion battery includes a positive electrode sheet, a negative electrode sheet, and a separator located between the positive electrode sheet and the negative electrode sheet. Furthermore, it also includes an electrolyte.

[0062] In some embodiments of the present application, similar to the negative electrode sheet, the positive electrode sheet also includes a positive electrode current collector and a positive electrode active layer located on the positive electrode current collector, and further includes a positive electrode active material, a conductive agent, and a binder. The positive electrode active material varies depending on the type of metal ion battery.

[0063] In some embodiments of the present application, the electrolyte may be at least one of an electrolyte solution and a solid electrolyte.

[0064] In some embodiments of the present application, the electrolyte includes an electrolyte salt and an organic solvent.

[0065] The electrolyte salt includes at least one of an inorganic salt and an organic salt, as long as it can be decomposed into metal ions and anions.

[0066] In some embodiments of the present application, the electrolyte lithium salt is selected from LiPF 6 At least one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium bis(fluorosulfonyl)imide (LiFSI). The electrolyte sodium salt is selected from NaPF 6 、NaFSI、NaClO 4 At least one of the following. The electrolyte potassium salt is selected from KPF 6 , KFSI or KTFSI.

[0067] In some embodiments of the present application, the organic solvent in the electrolyte includes at least one of esters, sulfones, ethers, and nitriles, including but not limited to propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylene glycol dimethyl ether (DME), fluoroethylene carbonate (FEC), diethylene glycol dimethyl ether, dimethyl sulfoxide, acetonitrile, etc.

[0068] In some embodiments of the present application, the lithium salt of the electrolyte is 3 mol / L LiPF 6 , dissolved in three solvents: EC, DMC and EMC, and the solvents are mixed in a volume ratio of 4:3:2.

[0069] In some embodiments of the present application, the sodium salt of the electrolyte is 1 mol / L NaClO 4 , dissolved in PC containing 5% FEC.

[0070] In some embodiments of the present application, the potassium salt of the electrolyte is 5 mol / L KFSI, dissolved in DME.

[0071] In some embodiments of the present application, the separator includes, but is not limited to, a single-layer or multi-layer film of one or more materials selected from polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), and glass fiber.

[0072] In some embodiments of the present application, the positive electrode sheet, the negative electrode sheet and the separator are wound, stacked or the like to obtain a battery cell, which is wrapped in a shell not limited to a soft shell and a hard shell, and sealed after contacting with an electrolyte to obtain a metal ion battery.

[0073] In the fifth aspect of the present application, an electrical device is provided, which includes the aforementioned metal ion battery. Electrical equipment refers to any device that can utilize electrical energy and convert it into mechanical energy, thermal energy, light energy, or other one or more energy-forming devices, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it may include but is not limited to mobile devices, electric vehicles, electric trains, ships, and satellites, etc. The mobile devices may be mobile phones, laptop computers, drones, sweeping robots, electronic cigarettes, etc.; the electric vehicles may be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0074] The naphthyl polycarboxylate organic material synthesized in the embodiments of the present application has the following advantages: (1) A simple one-step method is used to synthesize a green material with good electrochemical properties, which can be used for efficient metal ion storage. The preparation method is simple to operate, and the required raw materials are abundant in reserves and cheap, which can effectively reduce the cost of batteries; (2) The synthesized naphthyl carboxylic acid metal salt has abundant metal ion storage sites, exhibits a higher battery specific capacity, and the higher metal ion storage capacity can also better meet actual needs; (3) The cross-linking coating of the carbon-based material not only alleviates the volume expansion problem during the cycle, but also improves the conductivity of the material; (4) The carbonyl group contained in the naphthyl carboxylic acid forms a conjugated carbonyl group with the benzene ring. The carbonyl group has high reversibility during the electrochemical reaction. The corresponding chemical reaction can be stabilized by the conjugated structure, thereby improving the long-cycle performance and stability of the battery.

[0075] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] Figure 1 is Li in one embodiment of the present application 4 Fourier transform infrared (FT-IR) spectra of NTC and NTCA.

[0077] Figure 2 is Li in one embodiment of the present application 4Scanning electron microscopy (SEM) of NTC / CNTs.

[0078] Figure 3 is Li in one embodiment of the present application 4 After NTC / CNTs were used as negative electrode active materials to make lithium-ion half-cells, the -1 Typical charge and discharge curves at different current densities.

[0079] Figure 4 is Li in one embodiment of the present application 4 After NTC / CNTs were used as negative electrode active materials to make lithium-ion half-cells, the -1 Long cycle curves of current density. DETAILED DESCRIPTION

[0080] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0081] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0082] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0083] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0084] Example 1

[0085] This embodiment provides a naphthyl polycarboxylate organic material, specifically 1,4,5,8-naphthalenetetracarboxylic acid lithium / carbon nanotube material (Li 4 NTC / CNTs), the preparation steps are as follows:

[0086] (1) Weigh 4 mmol of lithium hydroxide and dissolve it in 100 ml of anhydrous ethanol solution, and stir it magnetically for 1 hour to obtain a LiOH solution; weigh 0.5 mmol of 1,4,5,8-naphthalenetetracarboxylic acid (NTCA) and dissolve it in 100 ml of a mixture of acetone and water (volume ratio 10:3), and stir it magnetically for 1 hour to obtain a NTCA solution.

[0087] (2) Weigh 12 mg of carbon nanotubes, add them to 20 ml of anhydrous ethanol, sonicate for 1 hour, stir for 1 hour, and then continue sonicating for 30 minutes until the carbon nanotubes are evenly dispersed in the anhydrous ethanol to obtain a CNT dispersion.

[0088] (3) Slowly add the CNT dispersion into the NTCA solution using a dropper and continue stirring for 2 hours to obtain a first mixed solution.

[0089] (4) While stirring, slowly add the LiOH solution into the first mixed solution using a dropper, and continue stirring for 4 hours to obtain a second mixed solution.

[0090] (5) Pour the second mixed liquid into the polytetrafluoroethylene liner and put it into a reaction kettle, transfer the reaction kettle into an oven for reaction at a temperature of 100° C. for 24 hours, and wait until the reaction temperature drops to room temperature to obtain a reaction liquid.

[0091] (6) The reaction solution was centrifuged at 9000 rpm for 10 minutes. Then, it was washed with ethanol and centrifuged for 5 times, and then placed in an oven for vacuum drying at 60°C for 48 hours. Finally, 1,4,5,8-naphthalenetetracarboxylic acid lithium / carbon nanotube material (Li 4 NTC / CNTs).

[0092] At the same time, lithium naphthalenetetracarboxylate (Li 4 NTC), the steps are as follows:

[0093] (1) 4 mmol of lithium hydroxide was weighed and dissolved in 100 ml of anhydrous ethanol solution, and magnetic stirring was performed for 1 hour to obtain a LiOH solution; 0.5 mmol of 1,4,5,8-naphthyltetracarboxylic acid (NTCA) was weighed and dissolved in 100 ml of a mixture of acetone and water (volume ratio 10:3), and magnetic stirring was performed for 1 hour to obtain a NTCA solution.

[0094] (2) While stirring, slowly add the LiOH solution into the NTCA solution using a dropper and continue stirring for 4 hours to obtain a mixed solution.

[0095] (3) Pour the mixed solution into a polytetrafluoroethylene liner and place it in a reactor, transfer the reactor into an oven for reaction at a temperature of 100° C. for 24 hours, and wait until the reaction cools to room temperature to obtain a reaction solution.

[0096] (4) The reaction solution was centrifuged at 9000 rpm for 10 minutes. Then, it was washed with ethanol and centrifuged for 5 times, and then placed in a vacuum oven for drying at 60°C for 48 hours. Finally, lithium naphthalenetetracarboxylate (Li 4 NTC).

[0097] Physical Characterization:

[0098] The raw material NTCA and the product Li 4 NTC is tested by Fourier transform infrared spectroscopy (FT-IR), and its spectrum is as follows Figure 1 As shown. 4 There is no obvious peak corresponding to CNTs in NTC / CNTs, so the spectrum directly gives Li 4 Fourier infrared spectrum of NTC. It can be seen that at 1721cm -1 The absorption peak at 1721 cm -1 The absorption peak at disappeared, proving that Li 4 The formation of NTC. At 1558 and 1364 cm -1 The absorption peaks at 4 Asymmetric stretching vibration peak v of NTC carboxylates as (-COO) and symmetrical stretching vibration peak v s (-COO).

[0099] At the same time, if Figure 2 As shown in the scanning electron microscope (SEM) image, the product Li 4 NTC / CNTs transfer Li 4 NTCs connect together to form a cross-linked network structure.

[0100] Electrochemical performance test - lithium ion half-cell performance test:

[0101] By Li 4 NTC / CNTs is used as the negative electrode material, and the metal lithium sheet is used as the counter electrode to assemble the lithium-ion half-cell. The battery performance is characterized to verify the Li 4 Lithium storage performance of NTC / CNTs materials.

[0102] Negative electrode preparation: Li 4 NTC / CNTs materials, conductive carbon black, and polyvinylidene fluoride (PVDF) were uniformly mixed together in a mass ratio of 6:3:1, ground for 30 minutes, and N-methylpyrrolidone (NMP) was added to make a paste slurry. Then, the slurry was evenly coated on a copper foil, followed by vacuum drying at 70°C for 24 hours; the dried copper foil was rolled and cut into discs with a diameter of 10 mm as the negative electrode, and a commercial lithium sheet was used as the counter electrode. The glass fiber membrane was cut into discs with a diameter of 16 mm and used as a diaphragm for standby use.

[0103] Preparation of electrolyte: weigh 9mmol LiPF 6 Dissolve in 3 ml of mixed solvent, the mixed solvent is ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 4:3:2, and stir well to obtain 3 mol / L LiPF 6 The electrolyte is ready for use.

[0104] Assembly: In a glove box protected by inert gas (the content of water and oxygen is less than 0.1 ppm), the prepared positive electrode, diaphragm, and negative electrode are tightly stacked in sequence, the electrolyte is dripped to completely soak the diaphragm, and then the stacked part is encapsulated into a button-type shell to complete the assembly of the lithium-ion half-cell.

[0105] Performance test: The battery charge and discharge test is carried out on the Xinwei battery test system, and the battery working window is 0.01~3V.

[0106] Figure 3 For this embodiment, Li 4 The lithium-ion half-cell made of NTC / CNTs has a high conductivity at 100 mA g -1 The typical charge and discharge curve under current density shows a clear voltage platform at ~1.1V / 1.2V.

[0107] Figure 4 For this embodiment, Li 4 The lithium-ion half-cell made of NTC / CNTs has a high conductivity at 200 mA g -1 Long cycle curve of current density. Figure 4 It can be seen that Li 4 The lithium-ion half-cell made of NTC / CNTs has a nearly consistent charge and discharge specific capacity at different cycle numbers, and the coulombic efficiency is close to 100%, showing stable cycle performance.

[0108] The half-cell of the above embodiment and the Li 4 NTC / CNTs are replaced by Li 4 The half-cell obtained by NTC uses 100mA g-1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0109] Table 1. Battery test data of Example 1 and Comparative Example 1

[0110]

[0111] Comparison of Example 1 and Comparative Example 1 shows that the Li 4 Although NTC also achieved good capacity retention, it did not form Li 4 The cross-linked structure of NTC and CNT through aromatic stacking is obviously inferior to that of Example 1 in terms of first effect and capacity retention rate.

[0112] Example 2-44

[0113] The 1,4,5,8-naphthalenetetracarboxylic acid in Example 1 was replaced by 1-naphthalenecarboxylic acid (Example 2), 2-naphthalenecarboxylic acid (Example 3), 1,4-naphthalene dicarboxylic acid (Example 4), 2,6-naphthalene dicarboxylic acid (Example 5), 1,5-naphthalene dicarboxylic acid (Example 6), 1,8-naphthalene dicarboxylic acid (Example 7), 1,3,5-naphthalene tricarboxylic acid (Example 8), 1,4,5-naphthalene tricarboxylic acid (Example 9), 2,4,5-naphthalene tricarboxylic acid (Example 10), 1,4,7-naphthalene tricarboxylic acid (Example 11), 1,2,8-naphthalene tricarboxylic acid (Example 12), 1,3,5,7-naphthalene tetracarboxylic acid (Example 13), 1,2,3,4-naphthalene tetracarboxylic acid (Example 14), 1,4,6,7-naphthalenetetracarboxylic acid (Example 15), 2,3,6,7-naphthalenetetracarboxylic acid (Example 16), 1,2,3,4,5-naphthalenepentacarboxylic acid (Example 17), 1,2,3,4,6-naphthalenepentacarboxylic acid (Example 18), 1,2,3,6,7-naphthalenepentacarboxylic acid (Example 19), 1,2,3,5,8-naphthalenepentacarboxylic acid (Example 20), 1,2,4,5,8-naphthalenepentacarboxylic acid (Example 21), 1,2,4,5,6,8-naphthalenehexacarboxylic acid (Example 22), 1,2,3,4,5,8-naphthalenehexacarboxylic acid (Example 23), 1,2,3,4,6,7-naphthalenehexacarboxylic acid (Example 24), 1,2,3,4,5,6,7- Naphthalene heptanoic acid (Example 25), 1,2,3,4,5,6,8-naphthalene heptanoic acid (Example 26), 1,2,3,4,5,6,7,8-naphthalene octacarboxylic acid (Example 27), 5-chloro-1-naphthalenecarboxylic acid (Example 28), 5-amino-1-naphthalenecarboxylic acid (Example 29), 6-hydroxy-2-naphthalenecarboxylic acid (Example 30), 5,8-dihydroxy-2-naphthalenecarboxylic acid (Example 31), 6-sulfonyl-2-naphthalenecarboxylic acid (Example 32), 4-nitro-1,8-naphthalene dicarboxylic acid (Example 33), 6-bromo-1,4-naphthalene dicarboxylic acid (Example 34), 3-aldehyde-1,5-naphthalene dicarboxylic acid (Example 35), 2-iodo-1,4,5-naphthalene tricarboxylic acid (Example 36), Example 36), 3-carbonyl-1,5,8-naphthalenetricarboxylic acid (Example 37), 2-mercapto-1,4,5-naphthalenetricarboxylic acid (Example 38), 3-hydroxy-1,5,8-naphthalenetricarboxylic acid (Example 39), 2-methyl-1,4,5,8-naphthalenetetracarboxylic acid (Example 40), 6-cyano-1,2,3,4-naphthalenetetracarboxylic acid (Example 41), 2-ethyl-1,4,5,6,8-naphthalenepentacarboxylic acid (Example 42), 6-chloro-1,3,4,5,7,8-naphthalenehexacarboxylic acid (Example 43), 6-acetic acid-1,2,3,4,5,7,8-naphthaleneheptacarboxylic acid (Example 44) were prepared by the same method as in Example 1 to obtain naphthyl polycarboxylate organic material.

[0114] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0115] Table 2. Battery test data of Examples 1 to 44

[0116]

[0117]

[0118]

[0119] Embodiments 45 to 47

[0120] The lithium hydroxide in Example 1 was replaced by lithium nitrate (Example 45), lithium chloride (Example 46), and lithium sulfate (Example 47) to prepare a naphthyl polycarboxylate organic material.

[0121] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0122] Table 3. Battery test data of Example 1 and Examples 45 to 47

[0123]

[0124] From the above results, it can be seen that the naphthyl polycarboxylate organic material prepared by using alkali metal base as alkali metal source in Example 1 exhibits more excellent electrochemical performance, and the first effect, reversible specific capacity and capacity retention rate are all the highest.

[0125] Embodiments 48 to 51

[0126] The amount of NTCA was fixed, and the amount of lithium hydroxide was adjusted so that the molar ratio of lithium hydroxide to 1,4,5,8-naphthalenetetracarboxylic acid in Example 1 was changed from 8 to 2 (Example 48), 4 (Example 49), 12 (Example 50), and 16 (Example 51) to prepare a naphthyl polycarboxylate organic material.

[0127] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0128] Table 4. Battery test data of Example 1 and Examples 48 to 51

[0129]

[0130] It can be seen from the above results that when the molar ratio of lithium hydroxide to carboxylic acid group in Examples 1, 50, and 51 is 2, 3, and 4, the first effect, reversible specific capacity, and capacity retention rate are relatively high.

[0131] Embodiments 52 to 60

[0132] The anhydrous ethanol (solvent A) used to dissolve LiOH in Example 1 is replaced with deionized water (Example 52) and a mixture of ethanol and water in a volume ratio of 1:1 (Example 53); the acetone aqueous solution (solvent B) with a volume ratio of 10:3 used to dissolve NTCA is replaced with anhydrous ethanol (Example 54), deionized water (Example 55), acetone (Example 56), ethylene glycol (Example 57), glycerol (Example 58), NN dimethylformamide (Example 59), and dimethyl sulfoxide (Example 60) to prepare a naphthyl polycarboxylate organic material.

[0133] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0134] Table 5. Battery test data of Example 1 and Examples 52 to 60

[0135]

[0136]

[0137] It can be seen from the above results that during the preparation process, compared with the embodiments using other solvents, the naphthyl polycarboxylate organic material prepared by dissolving the alkali metal source in ethanol and dissolving NTCA in a specific proportion of acetone and water in Example 1 exhibited better electrochemical performance, with the first effect, reversible specific capacity and capacity retention rate being the highest.

[0138] Embodiments 61 to 69

[0139] The mass of the carbon nanotubes was changed from 12 mg in Example 1 to 5 mg (Example 61), 10 mg (Example 62), and 15 mg (Example 63), and the single-walled carbon nanotubes were changed to multi-walled carbon nanotubes (Example 64), carbon nanofibers (Example 65), soft carbon (Example 66), hard carbon (Example 67), graphite (Example 68), and graphene (Example 69) to prepare naphthyl polycarboxylate organic materials.

[0140] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0141] Table 6. Battery test data of Example 1 and Examples 61 to 69

[0142]

[0143]

[0144] From the above results, it can be seen that under the same feed amount, the electrochemical performance of single-walled carbon nanotubes, hard carbon and graphene decreases in turn, and Example 1 using single-walled carbon nanotubes as carbon-based materials performs best. Comparing Examples 1 and 61-63, as the amount of single-walled carbon nanotubes increases, the first coulombic efficiency gradually increases, but the reversible specific capacity and capacity retention first increase and then decrease, and still perform best in Example 1.

[0145] Embodiments 70 to 75

[0146] The reaction temperature of step (5) of Example 1 was adjusted to 80°C (Example 70), 140°C (Example 71), and 180°C (Example 72) during the reaction time of 100°C for 24 hours, and the reaction time was adjusted to 12 hours (Example 73), 48 hours (Example 74), and 72 hours (Example 75) to prepare a naphthyl polycarboxylate organic material.

[0147] The naphthyl polycarboxylate organic material of the above example was prepared into a half-cell by the same method as in Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0148] Table 7. Battery test data of Example 1 and Examples 70 to 75

[0149]

[0150] Comparing Examples 1 and 70 to 72, as the reaction temperature increases, the first effect gradually increases, but the reversible specific capacity and capacity retention first increase and then decrease, and 100°C in Example 1 is the best. Comparing Examples 1 and 73 to 75, as the reaction time increases, the first effect, reversible specific capacity and capacity retention rate first increase and then decrease, and 24h in Example 1 is the best.

[0151] Embodiments 76 to 83

[0152] The metal source lithium hydroxide in Example 1 is replaced by sodium hydroxide, and the product Na 4 NTC / CNTs are used in sodium ion batteries (Example 76); replaced with sodium chloride, the product Na 4 NTC / CNTs are used in sodium ion batteries (Example 77); replaced with sodium nitrate, the product Na 4 NTC / CNTs are used in sodium ion batteries (Example 78); replaced with sodium sulfate, the product Na 4 NTC@CNTs are used in sodium ion batteries (Example 79); replaced with potassium hydroxide, the product K 4 NTC / CNTs are used in potassium ion batteries (Example 80); replaced with potassium chloride, the product K 4 NTC / CNTs are used in potassium ion batteries (Example 81); replaced with potassium nitrate, the product K 4 NTC / CNTs are used in potassium ion batteries (Example 82); replaced with potassium sulfate, the product K 4 NTC / CNTs are used in potassium ion batteries (Example 83).

[0153] The naphthyl polycarboxylate organic material of the above embodiment is prepared into a sodium ion battery or a potassium ion battery by a method similar to that of Example 1. -1 The charge and discharge rate (current density) is tested at a voltage range of 0.01 to 3V. The test results are as follows:

[0154] Table 8. Battery test data of Example 1 and Examples 76 to 83

[0155]

[0156] The use of alkali metal sources for sodium ion batteries and potassium ion batteries is similar to that of lithium ion batteries. When sodium hydroxide or potassium hydroxide is used for preparation, the battery obtained using this naphthyl polycarboxylate organic material has the best first efficiency, reversible specific capacity and capacity retention rate.

[0157] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. Naphthyl polycarboxylate organic material, characterized in that: It includes a naphthyl compound and a carbon-based material cross-linked with the naphthyl compound, and the structural formula of the naphthyl compound is as follows: Wherein, R and R′ are independently selected from at least one of hydrogen, halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl, sulfonic acid, substituted or unsubstituted C1-C3 alkyl, substituted or unsubstituted C1-C3 alkoxy, and the substituent of C1-C3 alkyl and C1-C3 alkoxy is selected from at least one of halogen, hydroxyl, amino, nitro, cyano, thiol, aldehyde, carbonyl, and sulfonic acid; x and y are independently selected from integers of 0 to 4, and x and y are not 0 at the same time; M 1 and M 2 are independently selected from hydrogen and alkali metals, wherein the alkali metal is any one of lithium, sodium and potassium, and x M 1 and y M 2 Not hydrogen at the same time.

2. The naphthyl polycarboxylate organic material according to claim 1, characterized in that R and R' are each hydrogen.

3. The naphthyl polycarboxylate organic material according to claim 1, characterized in that: x and y are each independently selected from integers of 1 to 3.

4. The naphthyl polycarboxylate organic material according to claim 1, characterized in that The naphthyl compound is an alkali metal salt of at least one selected from 1,3,5-naphthalenetricarboxylic acid, 1,4,5-naphthalenetricarboxylic acid, 1,5,8-naphthalenetricarboxylic acid, 1,3,5,7-naphthalenetetracarboxylic acid, 1,4,6,7-naphthalenetetracarboxylic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 1,2,3,4,6-naphthalenepentacarboxylic acid, 1,2,3,5,8-naphthalenepentacarboxylic acid, 1,2,4,5,8-naphthalenepentacarboxylic acid, 1,2,4,5,6,8-naphthalenehexacarboxylic acid, 1,2,3,4,5,8-naphthalenehexacarboxylic acid, 1,2,3,4,6,7-naphthalenehexacarboxylic acid, and 1,2,3,4,5,6,7,8-naphthaleneoctacarboxylic acid.

5. The naphthyl polycarboxylate organic material according to claim 1, characterized in that: The carbon-based material is selected from at least one of carbon nanotubes, carbon nanofibers, soft carbon, hard carbon, graphite, and graphene.

6. The naphthyl polycarboxylate organic material according to claim 5, characterized in that: The carbon-based material is carbon nanotube.

7. The naphthyl polycarboxylate organic material according to claim 6, characterized in that: The carbon-based material is single-walled carbon nanotube.

8. The naphthyl polycarboxylate organic material according to claim 1, characterized in that: Based on the total mass of the naphthyl polycarboxylate organic material, the content of the carbon-based material is 1 to 10 wt %.

9. The method for preparing the naphthyl polycarboxylate organic material according to any one of claims 1 to 8, characterized in that: The following steps are involved: The carbon-based material, naphthyl carboxylic acid and alkali metal source are mixed in a liquid phase, reacted at 80-180° C. for 12-72 hours, separated and dried to obtain the naphthyl polycarboxylate organic material.

10. The preparation method according to claim 9, characterized in that: The step of mixing the carbon-based material, naphthyl carboxylic acid and alkali metal source in a liquid phase comprises: Adding the dispersion of the carbon-based material dropwise into the solution of naphthyl carboxylic acid and mixing well to obtain a first mixed solution; The solution of the alkali metal source is added dropwise into the first mixed solution and mixed evenly to obtain a second mixed solution.

11. The preparation method according to claim 9, characterized in that: The alkali metal source is a base or a salt of an alkali metal.

12. The preparation method according to claim 11, characterized in that: The alkali metal source is an alkali metal base.

13. The preparation method according to claim 11, characterized in that: The alkali metal of the alkali metal source is any one of lithium, sodium and potassium.

14. The preparation method according to claim 9, characterized in that: The liquid phase is selected from at least one of anhydrous ethanol, ethylene glycol, glycerol, NN dimethylformamide, dimethyl sulfoxide, acetone, and deionized water.

15. The preparation method according to claim 9, characterized in that: The ratio of the molar amount of the alkali metal source to the molar amount of the carboxylic acid group in the naphthyl carboxylic acid is (0.5-12):

1.

16. The preparation method according to claim 15, characterized in that: The ratio of the molar amount of the alkali metal source to the molar amount of the carboxylic acid group in the naphthyl carboxylic acid is (2-12):

1.

17. A pole piece, characterized in that: The invention comprises a current collector and an active layer located on the current collector, wherein the raw material of the active layer comprises the naphthyl polycarboxylate organic material according to any one of claims 1 to 8 or the naphthyl polycarboxylate organic material prepared according to the preparation method according to any one of claims 9 to 16.

18. A metal ion battery, characterized in that: Including the pole piece as claimed in claim 17.

19. Electrical equipment, characterized in that: Includes the metal ion battery as described in claim 18.

Citation Information

Patent Citations

  • Preparation of graphite composite negative electrode material based on polycarboxylic acid potassium salt and application of composite negative electrode material to potassium ion battery

    CN114614002A